Detection of multidrug-resistant bacteria in the nasal cavities and evaluation of sinus disorders in patients undergoing Le Fort I osteotomy - Bárbara M. Mendes; Évelin S. Bortoli; Catherine B. Zaleski; Maila P. D. Martinelli; Vanessa F. Pascoal; Sílvia D. Oliveira (BMC, 2024)
Abstract Introduction Orthognathic surgery can lead to sinus alterations, including sinusitis, attributed to the exposure of maxillary sinuses during Le Fort I osteotomy. Furthermore, being a hospital-based procedure, there is potential risk of complications arising from bacteria prevalent in such environments. This study evaluated maxillary sinusitis occurrence and the presence of multidrug-resistant bacteria in the nasal cavity before and after orthognathic surgery. Methods Ten patients with dentofacial deformities underwent Le Fort I osteotomy. Clinical evaluations using SNOT-22 questionnaire were performed, and nasal cavity samples were collected pre-surgery and 3-6 months post-surgery to quantify total mesophilic bacteria and detect Staphylococcus aureus, Acinetobacter baumannii, and Klebsiella pneumoniae. Cone Beam Computed Tomography (CBCT) was performed pre- and post-operatively, and the results were evaluated using the Lund-Mackay system. This study was registered and approved by the Research Ethics Committee of PUCRS (No. 4.683.066). Results The evaluation of SNOT-22 revealed that five patients showed an improvement in symptoms, while two remained in the same range of interpretation. One patient developed post-operative maxillary sinusitis, which was not detected at the time of evaluation by SNOT-22 or CBCT. CBCT showed a worsening sinus condition in three patients, two of whom had a significant increase in total bacteria count in their nasal cavities. The Brodsky scale was used to assess hypertrophy in palatine tonsils, where 60% of the subjects had grade 1 tonsils, 20% had grade 2 and 20% had grade 3. None of the patients had grade 4 tonsils, which would indicate more than 75% obstruction. Two patients harboured S. aureus and K. pneumoniae in their nasal cavities. Notably, K. pneumoniae, which was multidrug-resistant, was present in the nasal cavity of patients even before surgery, but this did not result in maxillary sinusitis, likely due to the patients' young and healthy condition. Conclusion There was an improvement in signs and symptoms of maxillary sinusitis and quality of life in most patients after orthognathic surgery. However, some patients may still harbour multidrug-resistant bacteria, even if they are asymptomatic. Therefore, a thorough pre-operative assessment is essential to avoid difficult-to-treat post-operative complications.